Navigating the Nexus: Unraveling the Interconnected Dynamics of Religion, Ethnicity, Financial Constraints, and Mental Health among University Students in Pakistan - Dr. Samia Athar; Dr. Mehwish Aziz Khan; Aamir Ashfaq; Muhammad Sarim Zia (Al-Qanṭara, 2023)
The investigation of the interconnections between financial constraints and mental health among university students is of the utmost importance. The aim of this research endeavor is to investigate the correlation between financial constraints, ethnicity, and mental health among university students residing in Pakistan. Primary sources of data comprise the investigation. By means of regression analysis, this research ascertains that the degree of religious affiliation does not account for the observed discrepancies in mental health among the participants affiliated with universities in Pakistan in a statistically significant manner. On the contrary, ethnic groups including Punjabi, Baloch, and Sindhi demonstrate a noteworthy correlation, suggesting that their presence negatively impacts the mental well-being of students. The social quotient positively influences mental health, whereas the emotional quotient increases susceptibility to anxiety and stress. Additionally, the research demonstrates that financial limitations exacerbate the severity of mental health issues, potentially impeding students' academic performance.